Peroxisomes during postnatal development of mouse endocrine and exocrine pancreas display cell-type- and stage-specific protein composition - Colasante, Claudia; Bonilla-Martinez, Rocio; Berg, Timm; Windhorst, Anita; Baumgart-Vogt, Eveline; Justus Liebig University Giessen (My University, 2023)
Peroxisomal dysfunction unhinges cellular metabolism by causing the accumulation of toxic metabolic intermediates (e.g. reactive oxygen species, very -chain fatty acids, phytanic acid or eicosanoids) and the depletion of important lipid products (e.g. plasmalogens, polyunsaturated fatty acids), leading to various proinflammatory and devastating pathophysiological conditions like metabolic syndrome and age-related diseases including diabetes. Because the peroxisomal antioxidative marker enzyme catalase is low abundant in Langerhans islet cells, peroxisomes were considered scarcely present in the endocrine pancreas. Recently, studies demonstrated that the peroxisomal metabolism is relevant for pancreatic cell functionality. During the postnatal period, significant changes occur in the cell structure and the metabolism to trigger the final maturation of the pancreas, including cell proliferation, regulation of energy metabolism, and activation of signalling pathways. Our aim in this study was to (i) morphometrically analyse the density of peroxisomes in mouse endocrine versus exocrine pancreas and (ii) investigate how the distribution and the abundance of peroxisomal proteins involved in biogenesis, antioxidative defence and fatty acid metabolism change during pancreatic maturation in the postnatal period. Our results prove that endocrine and exocrine pancreatic cells contain high amounts of peroxisomes with heterogeneous protein content indicating that distinct endocrine and exocrine cell types require a specific set of peroxisomal proteins depending on their individual physiological functions. We further show that significant postnatal changes occur in the peroxisomal compartment of different pancreatic cells that are most probably relevant for the metabolic maturation and differentiation of the pancreas during the development from birth to adulthood.
Keywords: ddc:610